On Dynamic Behavior of a Nonideal Torsional Machine Suspension Structure - Alisverisci, G. Fusun; Bayiroglu, Huseyin; Balthazar, Jose Manoel; Palacios Felix, Jorge Luis; Rebello da Fonseca Brasil, Reyolando Manoel Lopes (SPRINGER, 2016)
We propose a mathematical model of a suspension, which is comprised of a bar, supposedly rigid, torsion spring, and an electric motor that turns the system due to the touch of a rotating mass, this mechanism has three DOF. The problem was modeled using Lagrange's equations. Subsequently, we calculated the natural frequencies of the system and find the linear normal modes of vibration. Due to the rotating mass of the engine's torque that was addressed in being constant, optimum engine, and also, is not constant, which is not ideal engine. Thus, we checked the stability of the system and hence, it was determined as a region of stability, where parameters were determined for numerical simulation using MATLAB (R) and MATHEMATICA software. The concept of nonlinear normal modes (NNMs) was introduced with the aim of providing a rigorous generalization of normal modes to nonlinear systems. Initially, NNMs were defined as periodic solutions of the underlying conservative system, and continuation algorithms were recently exploited to compute them. We use nonlinear normal modes but before a nonideal analysis to obtain chaos, instability, and so on.
Keywords: NONLINEAR NORMAL-MODES; Mathematics